Pengembangan LKPD Berbasis Project Based Learning untuk Memfasilitasi Kemampuan Berpikir Kritis Siswa di SMKN 9 Bengkulu Utara - Deddi Kristian (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This research is motivated by the low level of student engagement and suboptimal critical thinking skills in Pancasila Education learning at SMKN 9 Bengkulu Utara. The previously used student worksheets were conventional and had not integrated a learning model that encourages in-depth analysis and problemsolving activities. This study aims to develop a valid and practical Project Based Learning student worksheet that has the potential to facilitate the critical thinking skills of grade X students. The research method uses Research and Development with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of two expert validators, two teachers, and grade X students in limited and extensive trials. The research instruments were validation sheets and practicality questionnaires. The results showed that the Project Based Learning student worksheet obtained a very valid category with a percentage of 87% and was very practical based on student and teacher responses with percentages of 94% and 96.5%. The student worksheet was considered easy to use, attractive, and able to facilitate the implementation of project activities that support critical thinking indicators according to Facione, such as interpretation, analysis, evaluation, and inference. Thus, the developed student worksheet is suitable for use as teaching material to facilitate students' critical thinking skills.